Can the fiscal theory of the price level explain UK inflation in the 1970s? - Jingwen Fan; Patrick Minford (Cardiff University, Cardiff Business School, 2011)
We investigate whether the Fiscal Theory of the Price Level can explain UK inflation in the 1970s. We find that fiscal policy was non-Ricardian and money growth entirely endogenous in this period. The implied model of inflation is tested in two ways: for its trend using cointegration analysis and for its dynamics using the method of indirect inference. We find that it is not rejected. We also find that the model's errors indicate omitted dynamics which merit further research.
Keywords: E31; E37; E62; E65; 330; UK Inflation; Fiscal Theory of the Price Level; Cointegration test; Bootstrap simulation; Indirect inference; Wald statistic; Finanzpolitik; Öffentliche Ausgaben; Inflationsrate; Bootstrap-Verfahren; Großbritannien